Sniper - Taylor, Theodore (New York : Avon, 1991)
Fifteen-year-old Ben must cope alone when a mysterious sniper begins shooting the big cats in his family's private zoological preserve.
Booklist.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Young Adult
Keywords: Cats -- Fiction; Felidae -- Fiction; Zoos -- Fiction; Cats -- Fiction; Zoos -- Fiction